BRANCH PROFITABILITY IN MICROFINANCE INSTITUTION - Putranto, Adityo
PT Ibu Berdaya Fintek (Ibu Berdaya) is a fintech peer to peer lending service which connects urban lenders with micro entrepreneurs in rural areas that has obtained a business license from OJK. As of December 31, 2020, Ibu Berdaya has disbursed Rp 3,18 trillion (US$ 227 million) funds from mostly urban lenders to 569,417 women micro entrepreneurs across 18.900 villages in Java, Sulawesi, and Sumatra.